Bone Effects of Binge Alcohol Drinking Using Prepubescent Pigs as a Model. (12th September 2018) - Föger‐Samwald, Ursula; Knecht, Christian; Stimpfl, Thomas; Szekeres, Thomas; Kerschan‐Schindl, Katharina; Mikosch, Peter; Pietschmann, Peter; Sipos, Wolfgang
Abstract : Background: Although chronic alcohol consumption in adults is an established risk factor for osteoporotic fractures, there is a huge gap in our knowledge about bone effects of binge drinking in adolescents. The aim of this pilot study was therefore to assess skeletal effects of binge alcohol drinking using prepubescent pigs as a large animal model. Methods: Piglets aged 2 months were offered alcohol orally as a mixture of hard liquor and apple juice. Those with the highest propensity to drink alcohol were included in the experiment and received 1.4 g alcohol/kg bodyweight 2 times per week for 2 months (alcohol group); control piglets received apple juice in an identical manner. At the age of 4 months, the animals were euthanized; trabecular and cortical bone samples from the femur, the tibia, the humerus, and the fourth vertebral body harvested during necropsy were assessed by microcomputed tomography and dynamic histomorphometry. In addition, blood chemistry and blood alcohol determinations were performed. Results: Blood alcohol levels assessed 1 hour after alcohol administration were 0.99‰ ± 0.15, 1.12‰ ± 0.2, and 1.14‰ ± 0.18 at the ages of 2, 3, and 4 months, respectively. In the alcohol group, serum calcium and phosphate levels were decreased. In the femur, trabecular number and connectivity density were lower in the alcohol than in the control group, and in the humerus and the fourth vertebral bodies, an opposite pattern was seen for trabecular number and connectivity density, respectively. Cortical density was higher in the humerus and trabecular density higher in the tibia of the alcohol group compared to the control group. Cortical porosity was lower in the humerus of the alcohol group. No significant differences were seen for trabecular thickness, trabecular separation, bone volume fraction, and static and dynamic histomorphometric parameters. Conclusions: In this pilot study, we have assessed skeletal effects of binge alcohol drinking by using prepubescent pigs as a promising large animal model. Binge drinking has bone effects that are site‐specific. However, these data have to be verified in a larger study population.